A multi-resource data integration approach: identification of candidate genes regulating cell proliferation during neocortical development - Vied, Cynthia M.; Freudenberg, Florian; Wang, Yuting; Raposo, Alexandre A. S. F.; Feng, David; Nowakowski, Richard S. (Frontiers in Neuroscience, 2014)
Neurons of the mammalian neocortex are produced by proliferating cells located in the ventricular zone (VZ) lining the lateral ventricles. This is a complex and sequential process, requiring precise control of cell cycle progression, fate commitment and differentiation. We have analyzed publicly available databases from mouse and human to identify candidate genes that are potentially involved in regulating early neocortical development and neurogenesis. We used a mouse in situ hybridization dataset (The Allen Institute for Brain Science) to identify 13 genes (Cdon, Celsr1, Dbi, E2f5, Eomes, Hmgn2, Neurog2, Notch1, Pcnt, Sox3, Ssrp1, Tead2, Tgif2) with high correlation of expression in the proliferating cells of the VZ of the neocortex at early stages of development (E15.5). We generated a similar human brain network using microarray and RNA-seq data (BrainSpan Atlas) and identified 407 genes with high expression in the developing human VZ and subventricular zone (SVZ) at 8–9 post-conception weeks. Seven of the human genes were also present in the mouse VZ network. The human and mouse networks were extended using available genetic and proteomic datasets through GeneMANIA. A gene ontology search of the mouse and human networks indicated that many of the genes are involved in the cell cycle, DNA replication, mitosis and transcriptional regulation. The reported involvement of Cdon, Celsr1, Dbi, Eomes, Neurog2, Notch1, Pcnt, Sox3, Tead2, and Tgif2 in neural development or diseases resulting from the disruption of neurogenesis validates these candidate genes. Taken together, our knowledge-based discovery method has validated the involvement of many genes already known to be involved in neocortical development and extended the potential number of genes by 100's, many of which are involved in functions related to cell proliferation but others of which are potential candidates for involvement in the regulation of neocortical development.